Saberes Matemáticos Na Matéria Trabalhos Manuais: Processos De Escolarização Do Fazer, São Paulo E Rio De Janeiro (1890-1960) - Frizzarini, Claudia Regina Boen [UNIFESP] (2018)
This Research Aims At Analyzing How And What Mathematical Knowledge Are Articulated With The Subject Manual Work During The Primary School In The States Of São Paulo And Rio De Janeiro, Places Of Dissemination Of Education Ideals. The Research Period Is Delimited According To The Performance Of The Manual Works As A School Subject In The Primary Programs Of São Paulo And Rio De Janeiro States (1890-1950). The Theories Of Cultural History (Chartier, 2002, 2010, 2011), The History Of School Subjects And Teaching Purposes (Chervel, 1990), As Well As The Concepts Of Disciplinarization And "Knowledge For Teaching" And "Knowledge To Teach" (Hofstetter, Schneuwly, 2017) Are Employed In Analysis Of Primary Education Programs, Articles Of Pedagogical Journals And School Textbooks In The Construction Of A Historical Narrative About The Articulations. The Analysis Of The Sources Became Possible To Verify That These Articulations Are Not Exempt From The Educational Moment, Space And Teaching Purposes Of The Primary Schoo